2021
DOI: 10.1515/polyeng-2020-0301
|View full text |Cite
|
Sign up to set email alerts
|

Simvastatin-loaded graphene oxide embedded in polycaprolactone-polyurethane nanofibers for bone tissue engineering applications

Abstract: Here, the role of simvastatin-loaded graphene oxide embedded in polyurethane-polycaprolactone nanofibers for bone tissue engineering has been investigated. The scaffolds were physicochemically and mechanically characterized, and obtained polymeric composites were used as MG-63 cell culture scaffolds. The addition of graphene oxide-simvastatin to nanofibers generates a homogeneous and uniform microstructure as well as a reduction in fiber diameter. Results of water-scaffolds interaction indicated higher hydroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“…Several biopolymers, including poly (-caprolactone), poly(D,L-glycolic acid), poly(D,L-lactic acid), and PEG, have been approved for use in macroformulations by the FDA. 195,196 These biopolymers can be used to create polymeric nanoparticles that transport and discharge therapeutic constituents more effectively than unbound drugs. By utilizing the EPR effect or by adding targeting molecules to their surface, it is also possible to target specific disease areas.…”
Section: Polymer-based Nanocarriersmentioning
confidence: 99%
“…Several biopolymers, including poly (-caprolactone), poly(D,L-glycolic acid), poly(D,L-lactic acid), and PEG, have been approved for use in macroformulations by the FDA. 195,196 These biopolymers can be used to create polymeric nanoparticles that transport and discharge therapeutic constituents more effectively than unbound drugs. By utilizing the EPR effect or by adding targeting molecules to their surface, it is also possible to target specific disease areas.…”
Section: Polymer-based Nanocarriersmentioning
confidence: 99%
“…Simvastatin can accelerate bone regeneration by regulating BMP-2 gene expression and show an osteoinductive role through the Ras signaling pathway, and activate mitogen-activated protein kinases. Also, it can inhibit bone density reduction using estrogen receptor-alpha or BMP-2 induction [66,67]. Feng et al [68] demonstrated the capability of simvastatin to enhance osteoblast differentiation of mesenchymal stem cells in osteoporosis Sprague-Dawley rats.…”
Section: Statinsmentioning
confidence: 99%
“…They permit tissue formation with an inside layer of ECs surrounded by SMCs and their extracellular matrix. 18,19 Consequently, it seems the combination of Pl could yield some features analogous to the native tissue structure. This study aimed to create engineered vascular scaffolds based on PU-PCL-Pl and determine Pl effects on the scaffold's physicomechanical properties and endothelialization capacity in vitro.…”
Section: Pullulan As Promoting Endothelialization Capacity Of Electro...mentioning
confidence: 99%